A comparison between foot, handle forces and lower back positions between ergometers and on-water rowing with high performance rowers - Millar, S. K.; Reid, D.; Keeley, L. (New Zealand Journal of Sports Medicine, 2020)
Low back pain (LBP) is the most prevalent injury in rowing. Greater frequency of fixed rowing ergometers use has been associated with increased LBP, and sliding ergometers are proposed to reduce the stress on the spine. The purpose of this study was to examine the lumbar flexion curvature in conjunction with the foot and handle forces, on fixed and sliding ergometers versus on water conditions. Four elite female adult rowers volunteered for this study and completed a 1,000 meter maximal test on the stationary and fixed ergometers and then on water. Forces at the handle, and foot block were measured over the three trials. Lumbar curvature (% flexion) was calculated for the first half of the drive phase of stroke from the catch position. Results indicate that fixed rowing ergometers induced the greatest amount of lumbar flexion, with some reduction for sliding ergometers compared to on water. Handle forces on the fixed ergometer were greater than on water but no different for the sliding ergometer. There was a trend for the foot forces to be greater on the fixed ergometer. Rowers moved differently in the three conditions and this is most evident when comparing between the fixed ergometer to on-water rowing. These results indicate that those clinicians and coaches managing low back pain in rowers should advise that when returning to rowing following an episode of back pain, on water is the least stressful activity on the spine, fol-lowed by sliding ergs and finally the fixed ergometer.